The experience of buprenorphine implant in patients with opioid use disorder: a series of narrative interviews - Scurti, Pietro; Nunzi, Marco; Leonardi, Claudio; Pierlorenzi, Claudio; Marenzi, Roberta; Lamartora, Vincenzo (Frontiers in Psychiatry, 2023)
Background: This project used narrative medicine (NM) to assess the point of view of patients with Opioid Use Disorder (OUD) and the impact that addiction and a new treatment approach via buprenorphine implant had on their daily lives as compared with previous oral Opioid Agonist Therapy (OAT) Methods: Five patients with OUD undergoing treatment with a buprenorphine subcutaneous implant participated on a voluntary basis, provided their anonymity, by self-describing, in response to questions prompted by the clinician, their experience with this innovative therapy. The narratives were analysed according to standard NM methodology. Citations of patients' positive or negative experiences with traditional OAT and buprenorphine implant were classified according to 5 categories -patient's determination toward complete opioid abstinence, emotional impact, impact on life, smoothness of therapy, and therapy dependency -and quantified to obtain a picture of the overall therapy experience. Results: The analysis revealed the extent of the burden not only of addiction but also of the traditional OAT on patients' life, including relationships with family, job management, and free time. Conversely, the therapy with buprenorphine implant revealed a significant improvement in the quality of life of the patients, who also largely reported a positive emotional outcome during this therapy, as well as a solid determination to achieve complete recovery. Conclusions: This project illustrates the complex problems of living with OUD and provides insights into the added value of an innovative buprenorphine implant therapy that, due to its administration route and prolonged duration, allows patients to take an additional step toward total opioid abstinence and a complete recovery of daily life.